Subjective thermal strain impairs endurance performance in a temperate environment - Van Cutsem, J.; Roelands, B.; De Pauw, K.; Meeusen, R.; Marcora, S. (Physiology & Behavior, 2019)
• A heat pad was attached to the back of endurance athletes cycling to exhaustion. • The heat pad decreased time-to-exhaustion by 9% in a temperate environment. • The heat pad increased subjective thermal strain but not core body temperature. • The heat pad did not affect other physiological responses to cycling exercise. • Subjective thermal strain is an important determinant of endurance performance.